The Description of Teaching Reading Comprehension through Group Work and the Students’ Achievement at Eighth Grade of SMP Negeri 2 Gido in 2022/2023 - Trisman Lombu; Adieli Laoli; Yasminar A. Tel; Elwin P. Zebua (Universitas Muhammadiyah Enrekang, 2024)
Reading is one of the basic communicative skills to get information in the text. Reading comprehension is established to understand the meaning of the words, sentences, and paragraph sense relationship among ideas as it is. Teaching reading comprehension is a learning process that teaches students to understand a text more easily. In this learning process, the teacher gives instructions to students to form groups. Each group consists of four to five students. Students achievements in teaching reading comprehension are based on the structure of the text determined by the students. Therefore, the objectives of this research were to describe and to find out how the teacher teaching reading comprehension through Group work and Students’ Achievement at the eighth grade of SMP Negeri 2 Gido in 2022/2023. The method used in this research was descriptive qualitative. Data were obtained from observation checklist which were analyzed using the group work by the teacher and from interviews every student in classroom at the eighth grade students. After carrying out the analysis, it shows that the students' results in group work show that students are able to work together to understand the reading text, share the knowledge they each gain with their group friends. So they need the good method to encourage them to study effectively. And then the student achievement in teaching reading comprehension is that students are able to analyze the social function of the text and students are able to determine the structure of the text.